Effective Interventions on Improving Elderly's Independence in Activity of Daily Living: A Systematic Review and Logic Model - Motamed-Jahromi, Mohadeseh; Kaveh, Mohammad Hossein (Frontiers in Public Health, 2021)
The purpose of this systematic review was to investigate types of interventions or a combination of interventions can improve the elderly’s activity of daily living, and whether these interventions improve the elderly’s independence. After developing the search strategy, the various databases, including PubMed, Scopus, Cochrane Library and Science Direct were searched without time limit up to 16th October 2019. The Review Manager 5.1 software was used to determine the risk of bias. The standard processes include searching articles, literature searching, duplicate inclusion criteria screening, data extraction, critical appraisal, and study synthesis. Eight randomized controlled trials were included in the final analysis. Interventions were categorized Based on neuroscience-based Cognitive training, physical exercises, psychological empowerment, and combined interventions. After that it was determined their impact on instrumental and basic activity daily. As the findings show, the effect of the combined interventions is higher. Therefore, in order to increase the elderly’s independence in their instrumental and basic activities of daily living, the integrated interventions, including cognitive exercises, physical exercises, psychological empowerment, and adaptation of the physical, psychological, socioeconomic environment are suggested.